2015
DOI: 10.1002/bio.2941
|View full text |Cite
|
Sign up to set email alerts
|

Validated spectrofluorimetric method for determination of two phosphodiesterase inhibitors tadalafil and vardenafil in pharmaceutical preparations and spiked human plasma

Abstract: A valid, sensitive and rapid spectrofluorimetric method has been developed and validated for determination of both tadalafil (TAD) and vardenafil (VAR) either in their pure form, in their tablet dosage forms or spiked in human plasma. This method is based on measurement of the native fluorescence of both drugs in acetonitrile at λem 330 and 470 nm after excitation at 280 and 275 nm for tadalafil and vardenafil, respectively. Linear relationships were obtained over the concentration range 4-40 and 10-250 ng/mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…On reviewing literature, TMS was quantified by several methods, namely; TLC [16][17][18], HPLC in different matrices [18][19][20][21], capillary electrophoresis [16], spectrophotometry [16,[22][23][24], and electrochemical methods [16,25]. For TAD, several methods were reported for its determination includ-ing TLC [26][27][28][29], HPLC [26,[30][31][32][33][34][35][36], gas chromatography [26,37], capillary electrophoresis [26], spectrophotometry [26,[38][39][40][41], and electrochemical methods [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…On reviewing literature, TMS was quantified by several methods, namely; TLC [16][17][18], HPLC in different matrices [18][19][20][21], capillary electrophoresis [16], spectrophotometry [16,[22][23][24], and electrochemical methods [16,25]. For TAD, several methods were reported for its determination includ-ing TLC [26][27][28][29], HPLC [26,[30][31][32][33][34][35][36], gas chromatography [26,37], capillary electrophoresis [26], spectrophotometry [26,[38][39][40][41], and electrochemical methods [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Spectrofluorimetic methods of analysis are considered as sensitive and simple for the determination of many pharmaceutical active species in different samples [25,26]. To our knowledge there is no analytical method based on native fluorescence of SUM, in this study, it was found that SUM exhibits an emission fluorescence spectrum at about 350 nm after excitation at 225 nm in aqueous medium ( fig.…”
Section: Resultsmentioning
confidence: 63%
“…is method has a relatively long run time of 18 min and the LLOQ remained high (10 ng/mL) [11]. Abu El-Enin et al (2015) developed a spectrofluorimetric method to quantify vardenafil in human plasma and pharmaceutical products [12]. Despite the simple protein precipitation method with acetonitrile only, this method requires a large amount of human plasma (1 mL) to achieve an LLOQ of 10 ng/mL [12].…”
Section: Introductionmentioning
confidence: 99%